PENGELOLAAN KESAN JURU PARKIR WANITA DI KOTA PEKANBARU - Yolanda Safitri; Muhammad Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to find out how to manage the impression of the front stage and back stage of female parking attendants in Pekabaru. This research uses qualitative research with dramaturgy approach. By using purposive techniques in determining informants. Data collection techniques using interviews, observation, and documentation. The results of this study indicate, when on the front stage the female parking attendant has communication to customers both verbally in the form of greetings, non-verbal can be seen from the signs and attributes used. And at the back stage, the real life of female parking attendants at home and at work is very different, where at work they play a role as parking attendants that are no different from male parking attendants who look strong and tough, but when they are at the parking attendant's house women have strong maternal instincts, it can be seen from their ability to balance between work and as housewives who are responsible for their children. Keywords : Impression Management, Dramaturgy